Turbulent combustion of biomass syngas - Kwiatkowski, K.; Bajer, K.; Wędołowski, K. (Archives of Mechanics, 2012)
Biomass syngas, a low-calorific gas continuously produced in the process of biomass pyrolysis and gasification, a relatively little-known fuel, can be used for heat production in an industrial plant. However, stringent emission norms have to be fulfilled at all times. In this paper, we present numerical simulations of turbulent combustion of the biomass syngas. They show that strict norms can be kept and that the process does not need any additional oil-burners to sustain the mandatory temperature. We have created a 3D model of the real industrial syngas combustion chamber of complex geometry involving an axial co-flow jet and six additional air inlets to enhance the swirl and to promote the generation of vortices. We have run a series of non-premixed combustion simulations for the syngases produced from wood chips and from turkey feathers.